(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
When ingested, a drug is a harmful chemical that alters the physiology or psychology of creatures. Inhalation, injection, smoking, and dissolution beneath the tongue are all methods of drug ingestion. Drugs are derived from medicinal plants as well as organic synthesis. Several criminals operate under the guise of being drug dealers. "Internal carries, internal carries, internal carries, internal carries, internal Mule, body packer, and mule. Drug smuggling utilizing the human body as a conveyance is known as body packing. Cocaine and heroin are often wrapped in waterproof material. Latex or condoms, for example. People may see illicit drug use in the shape of body packers everywhere around us. Storing heroin and morphine in the form of gender pellets for an extended period might result in death. Penalties are determined by the Narcotic Psychotropic Substances Act of 1985. During a first conviction, the suspect faces a punishment of Rs 1-2 lakh and a minimum of 10 years in jail. If convicted again, a fine of 3-5 lakh rupees will be imposed, as well as a sentence of at least 20-30 years in jail. In this paper author talks about Body Carriers are at the heart of illegal trafficking. It is also found that package aspects such as color, packing materials, wrapper design, or innovations are more crucial considerations to consider when a buyer makes a purchasing choice. Finally, it was discovered that one of the most essential and strong factors influencing customer purchasing decisions is packing.